Peran Rhizobium dalam Kesuburan Tanah : Kajian Literatur - Apriyangsa Gulo; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Soil fertility is a key element in the sustainability of agricultural systems that support global food security. One important soil microorganism that plays a role in improving soil fertility is Rhizobium, a bacterium capable of biological nitrogen fixation through a symbiotic relationship with leguminosae plants. This bacterium not only contributes to increasing soil nitrogen availability by 30-50% but also helps reduce dependence on synthetic nitrogen fertilizers, which has implications for reducing greenhouse gas emissions. Nonetheless, the effectiveness of Rhizobium is strongly influenced by environmental conditions such as pH, salinity, and chemical pollutants, which can inhibit its symbiotic ability. Technological innovations, such as nano-based formulations and the development of superior strains, offer solutions to improve the efficiency of Rhizobium, but challenges such as high costs and lack of policy support remain. In addition, the widespread use of Rhizobium inoculants may disrupt the balance of the soil microbial ecosystem, requiring further research. Therefore, integration of technology, policy and farmer education is needed to optimally utilize the full potential of Rhizobium while mitigating environmental risks, to support a more sustainable agricultural system.